Identification of key driving forces of neonicotinoid insecticide residues in soils on a basin scale - Wang, JinZe; Fu, Nan; Li, CunLu; Li, ZiMeng; Wu, SiJia; Zhu, ZiYang; Han, BingJun; Liu, WenXin (Environmental pollution (1987), 2025)
Neonicotinoid insecticides (NEOs) have garnered global attention due to their widespread environmental residues and adverse effects on non-target organisms and human health. Characterizing the contamination patterns and identifying key driving forces influencing their residues are essential for effective pollution mitigation. This study examined the spatiotemporal distribution of NEOs in the agriculture-dominated Shaying River Basin, central China, and systematically evaluated the effects of multiple influencing factors on their accumulation in soils, as well as the multivariate interactions. Results showed that NEOs were widely detected in soils across the basin, with a detection frequency of 96.8 % and a median concentration of 24.1 ng/g, with imidacloprid, thiamethoxam, and clothianidin being the predominant compounds. NEO concentrations remained relatively consistent across seasons; however, contamination hotspots emerged more frequently during the dry season compared to the rainy season. Spatially, high NEO residues were observed in the central intensive agricultural region, while lower levels were found in the western mountainous areas and northern urban zones. Land-use type and the sown area of major food crops were identified as the leading predictors of NEO residues at the basin scale. In addition, soil pH, total organic carbon content, vegetable cultivation area, urbanization rate, and the total power of agricultural machinery also played important roles in regulating NEO contamination patterns. Pathway analysis further revealed that land use exerted a negative influence on soil NEO levels, while agricultural practices had a positive effect. NEOs in the soils of the Shaying River Basin pose a high ecological risk to non-target organisms, whereas the health risk of human exposure remains relatively low. Results from this study highlight the importance of rational land-use planning and the regulation of agricultural practices for effective management of soil NEO contamination. [Display omitted] •Neonicotinoids (NEOs) were widely detected in soils of the Shaying River Basin.•NEO hotspots emerged more frequently in the dry season than in the rainy seasons.•Land-use type and agricultural practices determined soil NEO residues at the basin scale.•NEOs in soils pose high ecological risks to non-target organisms.